Antioxidant Activity of Uli Banana Peel Extract (Musa x Paradisiaca L. AAB) - Fennia Ade Heriani; Suci Permata Sari; Ade Oktasari (Department of Chemistry - Universitas Bangka Belitung, 2021)
Banana plants are native to Indonesia wich are easy to find and have various benefits ranging from roots, stems, fruits until peel. Uli banana (Musa x Paradisiaca L. AAB) is one kind of processed banana that is easy to find. The study aimed to determine the antioxidant activity of banana peel extract of uli (Musa x Paradisiaca L. AAB) wich was carried out by maceration using n-hexane and ethanol solvents then fractionated with ethyl acetate and distilled water. Phytochemical screening showed that the uli banana peel extract contained flavonoids and tannins. Antioxidant activity was measured by using UV-Vis Spectrophotometry with the DPPH (2-2, diphenyl-1-picrylhydrazyl) method and IC50 (Inhibitory Concentration) test parameters. The results showed that the antioxidant activity of IC50 was 114.86 µg/ml which was classified as moderate antioxidant intensity.